hsa_circ_0026827 Promotes Osteoblast Differentiation of Human Dental Pulp Stem Cells Through the Beclin1 and RUNX1 Signaling Pathways by Sponging miR-188-3p - Ji, Fang; Zhu, Lanying; Pan, Jing; Shen, Zhecheng; Yang, Zhao; Wang, Jian; Bai, Xuebing; Lin, Yueting; Tao, Jiang (Frontiers in Cell and Developmental Biology, 2020)
Previous studies have found that circular RNA (circRNA) hsa_circ_0026827 plays a role during osteoblast differentiation, but the mechanism is unclear. The aim of this study was to illuminate the role of hsa_circ_0026827 in human dental pulp stem cells (DPSCs) during osteoblast differentiation. The results show that hsa_circ_0026827 expression significantly increased during osteoblast differentiation, while knockdown of hsa_circ_0026827 suppressed DPSC-derived osteoblast differentiation. microRNA (miRNA) expression profile analysis showed that downregulation of hsa_circ_0026827 promoted miR-188-3p expression. miR-188-3p downregulation restored osteogenic differentiation of DPSCs after hsa_circ_0026827 was silenced. Luciferase reporter assays verified that miR-188-3p was the target of hsa_circ_0026827 and also demonstrated that Beclin1 and RUNX1 were miR-188-3p downstream targets. miR-188-3p overexpression suppressed DPSC osteogenic differentiation by targeting Beclin-1-mediated autophagy and runt-related transcription factor 1 (RUNX1). In vivo studies using a heterotopic bone model also found that hsa_circ_0026827 overexpression plays an important role in promoting heterotopic bone formation. In conclusion, our research indicates that hsa_circ_0026827 promotes osteoblast differentiation of DPSCs via Beclin1 and the RUNX1 signaling pathways by sponging miR-188-3p, which suggests novel therapeutics for osteoporosis treatment.